Online learning after the COVID-19 pandemic: Learners’ motivations - Dos Santos, Luis M. (Frontiers in Education, 2022)
The COVID-19 pandemic has become a focus on reforming teaching, learning models and strategies, particularly in online teaching and learning tools. Based on the social cognitive career theory and the constructivist learning theory, the purpose of this study was to understand and explore the learning preference and experience of students’ online courses during the COVID-19 pandemic and the management after the COVID-19 pandemic from the students’ perspective. The study was guided by the following two research questions: 1) After the COVID-19 pandemic, why do the students want to continue their foreign language courses via an online platform and model? What are the motivations and reasons? 2) How would the students describe their experience of a foreign language course via an online platform and model? With the general inductive approach and sharing from 80 participants, the participants indicated that flexibilities and convenience, same outcomes and learning rigorousness, and interactive experiences with classmates from different parts of the world were the three main key points. The results of this study may provide recommendations to university leaders, department heads, and teachers to reform and upgrade their online teaching curriculum and course delivery options after the COVID-19 pandemic.